Donafenib intolerance in hepatocellular carcinoma: severe hand–foot skin reaction and successful switch to lenvatinib – a case report and literature review - Chen, Ying; Fu, Linglin; Song, Ping; Tan, Yinuo; Jin, Yuqi (Frontiers in Oncology, 2025)
BackgroundDonafenib is an approved multikinase inhibitor for hepatocellular carcinoma (HCC). However, cutaneous toxicity—particularly hand–foot skin reaction (HFSR)—may necessitate treatment interruption and compromise therapeutic continuity.Case presentationA 58-year-old man with HCC on a cirrhotic background developed abrupt onset of intensely painful plantar erythema with overlying desquamation 10–11 days after initiating donafenib. The lesions rapidly progressed, leading to impaired ambulation and were consistent with CTCAE grade 3 HFSR.Management and outcomeDonafenib was immediately discontinued, and the patient received short-term symptomatic management, resulting in prompt improvement of the acral lesions. He was subsequently transitioned to lenvatinib, which was well tolerated without recurrence of high-grade skin toxicity. The patient maintained clinical stability and was able to continue systemic anticancer therapy.ConclusionThis case highlights the importance of early detection and accurate grading of HFSR, timely treatment interruption, and mechanism-informed switching to an alternative tyrosine kinase inhibitor such as lenvatinib. It also underscores key differences in toxicity profiles between donafenib—associated with VEGFR/RAF-related cutaneous injury—and lenvatinib, which is more commonly linked to hypertension, diarrhea, and appetite or weight changes.